Elucidation of Antiviral and Antioxidant Potential of C-Phycocyanin against HIV-1 Infection through In Silico and In Vitro Approaches - Pratiksha Jadaun; Chandrabhan Seniya; Sudhir Kumar Pal; Sanjit Kumar; Pramod Kumar; Vijay Nema; Smita S Kulkarni; Anupam Mukherjee (MDPI AG, 2022)
Antiretroviral therapy is the single existing therapy for patients infected with HIV; however, it has drawbacks in terms of toxicity and resistance. Thus, there is a continuous need to explore safe and efficacious anti-retroviral agents. C-Phycocyanin (C-PC) is a phycobiliprotein, which has been known for various biological properties; however, its effect on HIV-1 replication needs revelation. This study aimed to identify the inhibitory effects of C-PC on HIV-1 using in vitro and in silico approaches and to assess its role in the generation of mitochondrial reactive oxygen species (ROS) during HIV-1 infection. In vitro anti-HIV-1 activity of C-PC was assessed on TZM-bl cells through luciferase gene assay against four different clades of HIV-1 strains in a dose-dependent manner. Results were confirmed in PBMCs, using the HIV-1 p24 antigen assay. Strong associations between C-PC and HIV-1 proteins were observed through in silico molecular simulation-based interactions, and the in vitro mechanistic study confirmed its target by inhibition of reverse transcriptase and protease enzymes. Additionally, the generation of mitochondrial ROS was detected by the MitoSOX and DCF-DA probe through confocal microscopy. Furthermore, our results confirmed that C-PC treatment notably subdued the fluorescence in the presence of the virus, thus reduction of ROS and the activation of caspase-3/7 in HIV-1-infected cells. Overall, our study suggests C-PC as a potent and broad in vitro antiviral and antioxidant agent against HIV-1 infection.